2013
DOI: 10.1109/tit.2013.2278691
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of All Nine Models of Channel Output Feedback for the Two-User Interference Channel

Abstract: In this paper, we study the impact of different channel output feedback architectures on the capacity of the two-user interference channel. For a two-user interference channel, a feedback link can exist between receivers and transmitters in 9 canonical architectures (see Fig. 2), ranging from only one feedback link to four feedback links. We derive the exact capacity region for the symmetric deterministic interference channel and the constant-gap capacity region for the symmetric Gaussian interference channel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In the case α ≥ 1, the bounds on active in characterizing the capacity region of the symmetric LD IC with noisy feedback. Therefore, the sum capacity in [26,Theorem 1], together with the bounds on the individual rates (22)(23)(24)(25), can lead to the same result as that in Theorem 1. It can be shown that the outer bound in (12f) in [21] is the same as our outer bound in (27) for the symmetric linear deterministic IC with noisy feedback.…”
Section: Comparison With the Linear Deterministic Ic Models With Smentioning
confidence: 69%
See 2 more Smart Citations
“…In the case α ≥ 1, the bounds on active in characterizing the capacity region of the symmetric LD IC with noisy feedback. Therefore, the sum capacity in [26,Theorem 1], together with the bounds on the individual rates (22)(23)(24)(25), can lead to the same result as that in Theorem 1. It can be shown that the outer bound in (12f) in [21] is the same as our outer bound in (27) for the symmetric linear deterministic IC with noisy feedback.…”
Section: Comparison With the Linear Deterministic Ic Models With Smentioning
confidence: 69%
“…Nevertheless, there is an alternative way to prove this outer bound. In the regime where α < 1, this outer bound is inactive due to the outer bound in (22); in the strong and very strong interference regimes, i.e. α ≥ 1, this outer bound follows from an interesting observation.…”
Section: A Capacity Regionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inner and outer bounds on the sum-capacity using the existing connections between channel-output feedback and conferencing transmitters have been presented in [31]. More general channel models, for instance when channel-outputs are fed back to both receivers, have been studied in [7], [32]- [34].…”
Section: Noisy Feedbackmentioning
confidence: 99%
“…Second, the case in which such observation is noisy corresponds to noisy channel-output feedback (NOF) [16], [17]. Third, the case in which such observation is a linear combination of the channel-outputs from both receivers subject to additive noise corresponds to wireless channeloutput feedback (WOF) [18]. The most general formulation is referred to as general channel-output feedback (GOF) [19]- [22].…”
Section: Introductionmentioning
confidence: 99%